Billie Eilish Select Songs: Psychological Study of the Depression of Youth Today - Makiling, Ralph Michael; Ilustrisimo, Kyle Joseph; Bernaldez, Tesalonica; Diones, Lito (International Journal of Language and Literary Studies, 2022)
This study investigates the depression of the youth today in Billie Eilish’s select songs, which specifically looks into the theme, lyrics, and symbols. The Study’s data was gathered by using the Psychodynamic Theory by Sigmund Freud, which talks about the personality of a human being, and Sigmund Freud is Psychoanalytic Literary Criticism, which helps in interpretatively analyzing the texts, and serves as a psychological mechanism to surface out hidden meanings, of literary work. Moreover, this study utilizes a qualitative method using a discourse analysis approach. The findings of the study show that the aspects of depression in the theme of Billie Eilish select songs are unresolved grief, hopelessness caused by loved ones’ abandonment, society’s toxic standards, family pressure, and isolation and insignificance; lyrics surface out being doubtful towards society’s good side, feeling unloved, disappointment in unfavourable circumstances experienced, anxiety being left behind, negative criticisms causing despair, self-pity, misery or loneliness, prolonged helplessness, and rejection as aspects of depression; and abandonment, mental breakdowns, longing for appreciation and acceptance, and heartbreak and loneliness are extracted as aspects of depression in symbols. In conclusion, Billie Eillish’s select songs depict the depression of the youth.